Morphological Analysis of Surface Degradation in Phenolic Friction Composites Using Image Processing Techniques - Yusubov, F.F.; Valiyev, V.K.; Akbarova, U.B. (Проблеми трибології, 2025)
This study investigates the surface degradation of phenolic-based brake friction composites under corrosive NaCl environments, emphasizing morphological analysis through digital image processing. The specimens were subjected to both vapor-phase and immersion conditions to simulate real-world corrosion scenarios. Surface changes were characterized via optical microscopy, Otsu-based grayscale binarization, and roughness profiling. The results indicated that vapor-phase exposure caused more uniform corrosion, but with smoother surfaces, while immersion led to localized and irregular damage. Post-corrosion dry friction tests showed a marked reduction in the coefficient of friction, attributed to surface smoothing and lubricious corrosion product formation